MANAJEMEN KEWIRAUSAHAAN BAGI WIRAUSAHA DI KOTA KUPANG - Apriana H j Fanggidae (Universitas Nusa Cendana, 2020)
The fundamental issue of every entrepreneur in Kupang is limited in its own capital, low labourskills, accounting and poor business management, lack of understanding of optimal inventories,limited market share, very limited business network and access to banking funding resources. Thereare a variety of reasons why it can happen: small businesses are not burdened by the demands ofshareholders who always want to dictate the management of business run, family members want tosacrifice short-term profits to gain long-term benefits, the level of flexibility of entrepreneurial torespond to challenges and opportunities without many obstacles, entrepreneurial can also convey animage of stability and provide continuity for customers Keywords : Management, Enterprenuership